Psycho-social and environmental correlates of location-specific physical activity among 9- and 15- year-old Norwegian boys and girls: the European Youth Heart Study - Anderssen Sigmund A; Klasson-Heggebø Lena; Ommundsen Yngvar (BMC, 2006)
Abstract Objective Little is known about the existence of independent location- or context specific forms of physical activity. This study sought to identify location-specific forms of physical activity in a sample of 9 and 15 years-olds Norwegian boys and girls, and examined their associations to psycho-social and environmental factors. Methods A cross-sectional study of 9 and 15-year-olds (N = 760; 379 boys and 381 girls) was conducted in which participants responded to a computer-based questionnaire (PEACH) tapping potentially location specific forms of physical activity as well as psycho-social and environmental correlates. Results Exploratory factor analysis indicated that the nine and fifteen year-olds self-reported their physical activity as located in three separate and specific contexts: a) school commuting, b) informal games play at school and c) organized sport, structured exercise and games play in leisure time. Dependent of location, psycho-social and environmental correlates explained between 15 and 55 percent of the variance in physical activity. The impact of peer support, enjoyment and perceived competence in physical activity generalized across the three locations. Enjoyment of physical education classes, parental support and teacher support, in contrast, confined to particular location-specific forms of physical activity. Generally, behavioural beliefs and environmental factors represented marginal correlates of all location-specific forms of activity. Conclusion Young peoples' physical activity was identified as taking place in multiply genuine locations, and the psychosocial correlates of their physical activity seem to some extent to be location specific. Results may inform intervention efforts suggesting that targeting specific sets of psycho-social factors may prove efficient across physical activity locations, gender and age groups. Others, in contrast may prove effective in facilitating location specific physical activity, in which age may come to moderate the efficiency of intervention efforts.